Peer victimization and aggression based on adolescence stages: an exploratory study - González-Cabrera, Joaquín; Montiel, Irene; Machimbarrena, Juan Manuel; Baridon Chauvie, Daniela; López-Carrasco, R.; Ortega-Barón, Jessica (Child Indicators Research, 2023)
Peer violence among adolescents raises social concern in schools due to the magnitude of the phenomenon and the associated psychological damage. Studies have shown that the prevalence of peer victimization and aggression and the types of associated behaviors vary across age groups. However, this problem has not yet been analyzed as a function of the different stages of adolescence (early adolescence, middle adolescence, late adolescence, and emerging adulthood). The primary objectives of the present study were to analyze the prevalence of victimization and aggression and to examine the differences in the participants’ total scores as a function of these four stages of adolescence. The sample was composed of 6,280 Spanish participants (63.2% male) between the ages of 11 and 22 years, from 24 non-university educational centers. The highest prevalence of peer violence (37.7% victims and 39.7% aggressors) was found in middle adolescence. However, the total scores of victimization and aggression were higher in early adolescence than in any other stage (p <.001), and they decreased progressively in the later stages. In all stages, the most frequent victimization and aggressive behaviors were those related to direct and indirect verbal violence, followed by those related to social, physical, and psychological violence. The prevalence of these behaviors also tended to decrease with age. This study implies that it is necessary to implement primary prevention programs before early adolescence. However, secondary prevention or intervention measures should also be implemented at later stages, especially in middle adolescence. In particular, programs should address all types of peer violence, taking into account the ages of the adolescents.
Keywords: adolescence; aggression; bullying; peer victimization; stage; Scopus; JCR